Diarrhoeal Disease of Children in Indonesia - Sunoto Sunoto; Adnan S. Wiharta; J. Sulianti Saroso (Paediatrica Indonesiana, 1978)
Diarrhoeal disease in infants and children up till now is still becoming a major problem with its high morbidity and mortality. There are too many factors which can play a role in causing this disease. But by giving Oral-glucose electrolyte Solution as soon as possible the case fatality rate can be reduced as low as possible. Whereas decreasing the morbidity still needs a very long time, since it has very multi-complex factors i.e. socio-economic condition, environmental and personal hygiene and sanitation, life style of people, belief, etc. The study on epidemiology, the influence of improvement of environmental sanitation and socio-anthropology is still very few, besides there is no satisfactory vaccin produced to prevent this disease. Meanwhile the worse of the case is that there is a tendency of decreasing breast-feeding in the big cities and to substiotute it with bottle-feeding.